PENINGKATAN KEMAMPUAN KEWIRAUSAHAAN, DIAGNOSIS PADA PERUSAHAAN MABEL X DI KABUPATEN LABUHANBATU - Hamamuddin Siregar (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2013)
In developed country is too many educational person and there is unemployee, so that why entrepreneurship is important to solve it. Development will be succed if entrepreneur work for them because recource of goverments’s limited. Goverment will not able to do all developing factors because need a big fun allocation, man-power, and inspection. In this era, the company has been expected to manage their company to be profesional base on available resources. The company will be called developed if they can use optimalization resources.